Higher-Order Recombination Processes in Argon Ions Observed via X-ray Emission in an EBIT - SPARC Collaboration (2022)
Funding Information: W.B.-N. acknowledges the GET_INvolved Programme at FAIR/GSI and the JIPhD program through contract POWR.03.05.00-00-Z309/17-00. Publisher Copyright: © 2022 by the authors.